Effectiveness of acid-tolerant antagonist-based biofungicide in the control of basal stem rot disease caused by ganoderma in oil palm seedlings on peat soil - Supriyanto; Sulistyowati Henny; Arifin Nur; Ruliyansyah Agus; Haris Ramadahan Tris (BIO Web of Conferences)
Oil palm is an important plantation commodity in Southeast Asia. As the world’s largest palm oil producer, Indonesia has always been associated with global warming because most of its plantation areas are on peatlands and their management is considered not environmentally friendly. In addition to land fertility problems, a serious problem in peatland oil palm cultivation is basal stem rot disease caused by the Ganoderma fungus. Until now, there has been no effective method to control this disease. Biological control is an environmentally friendly alternative method and is the focus of current development, but for peatland conditions, its development is limited by the ultra-low peat pH factor. This study aims to determine the effectiveness of biofungicides based on acid-tolerant antagonists in controlling basal stem rot disease in oil palm seedlings on peat soil. The study was conducted by testing a bio-fungicide formulation in powder formulation containing 3 isolates of acid-tolerant antagonists, namely Trichoderma viride B3J19, Trichoderma harzianum E4J8, and Trichoderma harzianum 13EJ15. Testing was carried out on oil palm seedlings in greenhouses and fields. The results in the greenhouse showed that after six months of observation, bio-fungicides were able to reduce the intensity of the disease by 13.34% with 1 application, while 3 applications were 66.67% compared to the positive control. Meanwhile, in the field, the use of bio-fungicides with 1 application could reduce the intensity of disease by 27.29%, while 3 applications were 90.90%. These results indicate that bio fungicides in powder formula containing acid-tolerant antagonists have the potential to be used as biological control agents for oil palm basal stem rot disease caused by Ganoderma in peatlands.